Stevens' Handbook of Experimental Psychology 2002
DOI: 10.1002/0471214426.pas0114
|View full text |Cite
|
Sign up to set email alerts
|

Touch and Haptics

Abstract: This chapter describes the psychophysics of touch—how tactile abilities and perceptions are measured, and what those measurements reveal about the somatosensory system. The ability to discern spatial aspects of tactile stimuli, such as how many are present and where they are on the skin, has been extensively studied: A key finding in this area is that resolution acuity predicts performance on a range of other tasks. Researchers have also examined temporal aspects of touch, especially through the use of vibrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Human mechanoreceptors found in the skin mediate tactile perception through mechanical stimulation obtained by direct contact with external stimuli in the environment ( [3]) or, in the case of telemanipulation, via contactors present in tactile interfaces which are used to feed back the tactile properties from the remote environment (e.g. [4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…Human mechanoreceptors found in the skin mediate tactile perception through mechanical stimulation obtained by direct contact with external stimuli in the environment ( [3]) or, in the case of telemanipulation, via contactors present in tactile interfaces which are used to feed back the tactile properties from the remote environment (e.g. [4][5][6]).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to learn how the perceived orientation of a tactile stimulus is affected when the body site to be stimulated changes its orientation in space. Although there have been hundreds of studies that deal with various spatial aspects of touch, such as acuity, localization, distance, and motion, relatively little attention has been paid to the perceived orientation of tactile stimuli (see Greenspan & Bolanowski, 1996; Hollins, 2002 for reviews of tactile perception). A notable exception is a study by Anstis and Tassinary (1983), who demonstrated that the perceived orientation of an edge that stimulates the lips varies with distortion of the lips.…”
mentioning
confidence: 99%